2013
DOI: 10.1063/1.4799273
|View full text |Cite
|
Sign up to set email alerts
|

Isomorph invariance of Couette shear flows simulated by the SLLOD equations of motion

Abstract: Non-equilibrium molecular dynamics simulations were performed to study the thermodynamic, structural, and dynamical properties of the single-component Lennard-Jones and the Kob-Andersen binary Lennard-Jones liquids. Both systems are known to have strong correlations between equilibrium thermal fluctuations of virial and potential energy. Such systems have good isomorphs (curves in the thermodynamic phase diagram along which structural, dynamical, and some thermodynamic quantities are invariant when expressed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…Although more work is needed in this regard, there are strong indications that the answer is in the affirmative. For instance, simulations have shown that isomorphs exist for some liquids under nanoconfinement 67 , as well as for liquids undergoing a linear or non-linear shear deformation described by the so-called SLLOD equations of motion 68 . In reference to experiments, consider the transition between the nematic and isotropic phases of a liquid crystal.…”
Section: Discussionmentioning
confidence: 99%
“…Although more work is needed in this regard, there are strong indications that the answer is in the affirmative. For instance, simulations have shown that isomorphs exist for some liquids under nanoconfinement 67 , as well as for liquids undergoing a linear or non-linear shear deformation described by the so-called SLLOD equations of motion 68 . In reference to experiments, consider the transition between the nematic and isotropic phases of a liquid crystal.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the relevant phase diagram acquires a third dimension defined by the shear rate. The density-temperature relation of the SLLOD-generalized isomorphs turned out not to involve the shear rate [18], however, a non-trivial fact that follows from Eq. (19).…”
Section: B Extending the Isomorph Conceptmentioning
confidence: 99%
“…Another application of Eq. (9) is for extending the isomorph concept to nonlinear flows described by the SLLOD equation of motion [18]. In this case the relevant phase diagram acquires a third dimension defined by the shear rate.…”
Section: B Extending the Isomorph Conceptmentioning
confidence: 99%
See 2 more Smart Citations